Fire history in relation to site type and vegetation in Vienansalo wilderness in eastern Fennoscandia, Russia - Wallenius, Tuomo H; Kuuluvainen, Timo; Vanha-Majamaa, Ilkka (Canadian Journal of Forest Research, 2004)
A wildfire area in a boreal forest landscape dominated by Pinus sylvestris L., in the Vienansalo wilderness area in eastern Fennoscandia, was examined for its spatial characteristics and fire history. The boundaries of the 360-ha fire that occurred in 1969 were mapped, and the vegetation types of burnt and unburnt areas were inventoried. Fire history was investigated in 40 study plots, and fire scars, tree ages, and charcoal in peat or soil were used for evidence of past fires. The complex shape of the 1969 fire and the detected small-scale variation in past fire frequencies were concordant with the existing small-scale variation in site moisture and vegetation characteristics in the area. Moist depressions, swamps, and more fertile forest patches dominated by Picea abies (L.) Karst. often did not burn when the nearby dryish forest type did. There was also temporal variability in fire frequency. An abrupt increase in the number of fires occurred in the late 17th century. In the mid-19th century, both the number of fires and the annually burnt area in the region decreased. Our results show that in the examined wildfire area, there has been considerable and consistent small-scale spatial variation in fire frequency and that historical fire regime evidently has been strongly affected by human activity.